Hall mobility of charge carriers in films of (PbX)₁₋x (Sm₂X₃)x semiconductors formed on porous silicon - Hasanov, H.A.; Murguzov, M.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Presented paper is devoted to studying the methods to prepare epitaxial films of (PbX)₁₋x(Sm₂X₃)x − (X – S, Se, Te; x = 0.04) semiconductors and to examine the Hall mobility of charge carriers in these films. It is revealed that the derived dependences μH (T) for the samples on values of the exponential coefficient ν = 1.7-2.8 testify the temperature course of mobility in the majority of samples and can be explained via the dispersion of acoustic oscillations in the lattice and presence of a temperature dependence on the effective mass.